Land Insecurity and its Implications on the Sustainable Social Development of the Populations of Greater Lomé and Atakpamé (Togo) - ADJAYI, Komi Arsène Fulbert; KPOTCHOU, Koffi; NASSI, Karl Martial (Journal of Ecohumanism, 2024)
The spatial dynamics of greater Lomé and Atakpamé lead to land pressures marked by increased demands for building plots. These desires for land create land insecurity, the implications of which disrupt the social development of populations. The objective of This item is to explain how land insecurity and its implications influence the social evolution of the populations of greater Lomé and Atakpamé. To achieve this, this research used quantitative and qualitative approaches based respectively on questionnaire administration and individual interview techniques. In total, 97 people victims of land insecurity were interviewed in greater Lomé compared to 89 in Atakpamé. The results from field studies showed that in greater Lomé, land insecurity is caused by double sales of land, eviction and expropriation. In Atakpamé, they manifest themselves in the selling off of arable land and the clandestine sale of inheritance land. As a result of these insecurities, buyers, whether from greater Lomé or Atakpamé, have lost their land and are forced to return, for some, to rental properties and for others, to family homes. Also, the loss of property rights on land has caused, among the populations of Atakpamé, the cessation of income-generating activities based mainly on agriculture. These situations have made buyers vulnerable and destabilized their social and economic development. Which plunges them into long-term precariousness.